Analyzing The Development of Cashless Society Using the Structural Equation Modeling - Muhammad Nurdin; Adji Fernandes; Eni Sumarminingsih; Solimun; Muhammad Ullah (Universitas Negeri Semarang, 2024)
Payment systems continue to evolve alongside advancements in information technology, driving the digitization of financial services and payment instruments. This study examines the influence of Psychological, Socio-Cultural, and Personal Factors on adopting electronic money and the growth of a cashless society, with Financial Technology as a moderating variable. The research involved 1,000 Bank BNI customers in the Jabodetabek area (Jakarta, Bogor, Depok, Tangerang, and Bekasi) actively using BNI Mobile Banking services. The analytical methods employed include Discourse Network Analysis and Structural Equation Modeling to develop a comprehensive analysis model. The results indicate that psychological and personal factors—such as motivation, perception, learning, positive attitude, modern lifestyle, and openness to change—significantly influence electronic money usage. However, socio-cultural factors do not exhibit a significant impact, primarily due to persistent cash usage habits and a lack of trust in technology. This study highlights the need for financial education to promote awareness of electronic money benefits and security, develop tailored financial products, and enhance regulatory collaboration between the government and relevant institutions.